A Deal over Dirt - Lange, Sophie (Worldwide Waste, 2020)
From a German-German Bargain to the Creation of an Environmental Problem in the 1980s In the 1970s, West Berlin started to transport its waste to East-German dumpsites. By the 1980s, Hamburg and other West German municipalities had followed suit, depositing their waste in Schönberg landfill, a waste disposal site situated in the German Democratic Republic (GDR) barely five kilometers from the German-German border. What began as an inner-German agreement with benefits for both sides soon developed into an environmental problem for the West German government. This article focuses on the strategies with which the Federal Republic of Germany (FRG) tried to assuage critical voters and cope with a dumping ground at its border. It is argued that because of the demands for political action by the people living close to the dump the ‘greening’ of politics, which means the inclusion of environmental concerns on the political agenda, produced ambiguous results.